Evaluation of the improvement in sexuality in women undergoing treatment for urinary incontinence - Espitia De La Hoz, Franklin José (2018)
Urinary incontinence (UI) affects 1 in 4 women. It can present at any age; its frequency increases at menopause. There are many factors involved in its appearance, but the weakening of the pelvic floor is the main cause. Objective: To analyze the differences in UI management with rehabilitation and laser use, and their influence in the sexuality of the women being treated. Design: Clinical, randomized, prospective, uncontrolled and open trial of patients who consulted at Clinica La Sagrada Familia, Armenia, Quindío, Colombia. Material: Women diagnosed with urinary incontinence were treated between January 2015 and April 2017. Results: We analyzed 45 women, mean age 47.1 ± 9.9 years. In the total population studied, the prevalence of stress incontinence was 55.5%, mixed UI presented in 35.5% and urge incontinence, in 8.8%. 86.6% of patients had vaginal laxity; in 28.8%, the UI occurred during intercourse, and 31.1% had anterior prolapse stage 2 or higher. The Female Sexual Function Index was 26.4 ± 5.1 points in the general population. At the beginning of treatment, group A had an index value of 27.3 ± 5.7 and group B, 26.7 ± 5.4. 18 weeks after the last session, it was 30.9 ± 5.1 and 32.7 ± 3.3, respectively. We observed an initial prevalence of sexual disorders of 86.6% in the general population; at the end of the treatment, it reduced to 15.5%. Conclusions: Rehabilitated women had a greater improvement in sexual response. The effectiveness of laser is superior to that of rehabilitation in the management of UI.